Ephaptic conduction molding memory engrams - A. Rabinovitch; R. Rabinovitch; D. Braunstein; E. Smolik; Y. Biton (BMC Biology)
Abstract Background Memories are programmed in the brain as connected neuronal ensembles called engrams. However, the method by which the brain forms engrams during memory encoding is not understood. Results We have created a mechanistic mathematical model showing a possible method of the encoding process. Our model is based on the cellular automata approach, which can specifically distinguish between neurons operated on by the synaptic and those operated on by the ephaptic modes. This feature allows us to confirm that the ephaptic mode induces the formation of repeating collections of operating neurons (sub-engrams) that can become memory-preserving entities, and the synaptic influence is manifested by molding these sub-engrams by pruning small ones and size-increasing and rounding larger ones to form the engrams’ final structures. Conclusions Ephaptic and synaptic dual-participation in the memory encoding process was exhibited. The sequence of activities was unveiled. We also speculate on possible procedures the brain can employ to enable the ephaptic mode to overtake the normal, synaptic-dominating one.